2021
DOI: 10.3390/s21082661
|View full text |Cite
|
Sign up to set email alerts
|

Gait Parameters Measured from Wearable Sensors Reliably Detect Freezing of Gait in a Stepping in Place Task

Abstract: Freezing of gait (FOG), a debilitating symptom of Parkinson’s disease (PD), can be safely studied using the stepping in place (SIP) task. However, clinical, visual identification of FOG during SIP is subjective and time consuming, and automatic FOG detection during SIP currently requires measuring the center of pressure on dual force plates. This study examines whether FOG elicited during SIP in 10 individuals with PD could be reliably detected using kinematic data measured from wearable inertial measurement u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In parallel with the improvement of FoG, the gait analysis in our study demonstrated an improvement of stride length, turn duration, and turn velocity, confirming the strict relationship between FoG and specific gait parameters [ 37 , 38 , 39 ] and supporting the theory of a higher threshold for the improvement of axial motor symptoms when compared with appendicular symptoms like limb tremor, rigidity, and bradykinesia.…”
Section: Discussionsupporting
confidence: 84%
“…In parallel with the improvement of FoG, the gait analysis in our study demonstrated an improvement of stride length, turn duration, and turn velocity, confirming the strict relationship between FoG and specific gait parameters [ 37 , 38 , 39 ] and supporting the theory of a higher threshold for the improvement of axial motor symptoms when compared with appendicular symptoms like limb tremor, rigidity, and bradykinesia.…”
Section: Discussionsupporting
confidence: 84%
“…Other relevant neural inputs include prolonged beta burst durations, which are related to disease severity, bradykinesia, and freezing of gait (FOG) (Tinkhauser et al, 2017;Anidi et al, 2018;Kehnemouyi et al, 2021). aDBS can also be driven by relevant behavioral inputs, such as tremor intensity or gait kinematics (Malekmohammadi et al, 2016;Cagnan et al, 2017;Herron et al, 2017;O'Day et al, 2020;Diep et al, 2021). The goal of therapy will determine the rates, at which DBS intensity is adjusted: slow ramps will adjust DBS intensity based on the time course of the onset and offset of medication doses, whereas faster ramps may respond to beta burst durations, and stochastic events such as tremor or FOG (Arlotti et al, 2018;Petrucci et al, 2020aPetrucci et al, ,b, 2021.…”
Section: Advances In Adaptive Deep Brain Stimulation Optimizing Subth...mentioning
confidence: 99%
“…DeepFOG has valid characteristics as an important telemedicine tool to inform doctors about the frequency of FoG events of their patients. In a further publication by Diep et al 41 used a FoG predicting technique in ten PD patients through the acquisition of kinematic data, measured by wearable shank-positioned Inertial measurement unit (IMU) sensors. Patient movements were analyzed during a stepping in place (SIP) test.…”
Section: Monitoring and Detecting Devicesmentioning
confidence: 99%